(untitled) (Polis (Santiago), 2019)
The Nordic Enabling Welfare State has been proposed as a modality for further development of social democracy. A key feature of this proposal relates to strengthening human capacities on the basis of “capacity cultivating public services”. This intersects systemically with the economic and technological development of a society of dynamic and innovative knowledge, making it possible to successfully face new challenges and demands. The purpose of the theoretical review carried out in this article is to uncover the central features of the complex dynamics that concur in the indicated phenomenon. It also contributes to a serious theoretical approach to the relevance for Latin America, in a broad sense, of the Nordic Enabling Welfare State and its development of human capabilities, and, in particular, to the revitalization of social democratic debates in the region.